KINERJA PELAYANAN RUMAH SAKIT DAERAH MADANI KOTA PEKANBARU - Savira Aulia; Mayarni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The civil area hospital is one of the hospitals that provides health services for people in the city of Pekanbaru, which always develops and complements health infrastructure according to community needs. The research objective was to determine and analyze the form of service performance of the Madani Regional Hospital in Pekanbaru City and to analyze the factors that hinder the service performance of the Madani Regional Hospital in Pekanbaru City. This study uses the organizational performance theory of Agus Dwiyanto (2008) which uses 5 indicators, namely: productivity, service quality, responsiveness, responsibility and accountability. The research method used is a qualitative research method with data collection techniques interviews, observation and documentation. The results showed that the performance of civil service hospitals in providing health services was not optimal. In terms of productivity, service quality, responsiveness, responsibility and accountability. Factors that hinder the performance of the Madani Regional Hospital in Pekanbaru City are human resources, facilities and infrastructure and limited funds. This has an influence on the performance of hospital services, such as human resources moving from health centers who have not been able to adapt to the work culture of the hospital.Keywords: Performance, Service, Hospital